EFFECT OF TIMES OF NITROGEN FERTILIZER APPLICATION ON GROWTH AND PROTEIN YIELD IN BREAD WHEAT (Triticum aestivum L,) UNDER NORTHERN AREA'S CONDITIONS - Mahfood Abdul-Kadir Mohammad; Rookan Katta Eisa (Mesopotamia Journal of Agriculture)
A field experiment was conducted during the two growing seasons (2009-2010)/(2010-2011) at Al-Khazer location/Kalak (50 Km/to north Mosul city to study the effect of four times of nitrogen fertilizer application (All amounts of nitrogen applied at sowing; All amounts at tellering stage, 1/2 amount at sowing and 1/2 amount at tellering, and the other 1/2 amount at tellering and the other 1/2 amount at booting stage) using five of bread wheat varieties (Ipa 95, Ipa 99, Tmoz 2, Sham 6 and Noor). The experiment was set out as a Randomized completely block design (R,C,B,D) with three replication. The most important results could be summarized as follows :cultivars differed significantly in all studied characters and for both seasons, Sham 6 surpass significantly in percentage and yield of protein. The time of nitrogen fertilizer application affected significantly all characters for both seasons. The highest values were observed when nitrogen fertilizer applied 1/2 amount at tillering stage and 1/2 amount at booting stage. The number of days to 50% spike emergence and leaves area significantly Increased when nitrogen fertilizer was applied at tillering stage. The binary interaction between varieties and timing of nitrogen fertilizer application showed significant differences for most characters. The interaction between sham 6 and the time of nitrogen Fertilizer application at tillering and booting stage was surpass on percentage and protein yield and leaves area in the first season. The interaction between Ipa 99 and nitrogen fertilizer application at tillering and booting stage gave surpass in plant high and protein yield in the first season, where as the interaction between verity Noor with the nitrogen fertilization at sowing had the least number of days to 50% spike emergence in the two seasons. On the other hand variety Ipa 95 had a higher values in leaves area in the first season and in the number of tillers in the second season as compared with all other varieties,